Krebs von den Lungen-6 surveillance in immune checkpoint inhibitor-induced pneumonitis - Isamu Okamoto; Kazuya Tsubouchi; Ryosuke Matsukane; Shoji Nakamura; Haruna Minami; Yasuto Yoneshima; Kojiro Hata; Sai Yasukochi; Kimitaka Suetsugu; Takeshi Hirota (Journal for ImmunoTherapy of Cancer)
Background The immune-related adverse event (irAE), pneumonitis, is a potentially fatal complication of immune checkpoint inhibitors (ICIs). Preventing its progression is crucial, emphasizing the need for effective screening tests. We evaluated the feasibility of using Krebs von den Lungen-6 (KL-6), a marker for interstitial pneumonitis, as a screening tool for pneumonitis.Methods We examined 500 patients with cancer divided into two groups: those with cancer other than non-small cell lung cancer (NSCLC) (Group 1, n=382) and those with NSCLC (Group 2, n=118). KL-6 levels were monitored before and during ICI treatment and analyzed for their correlation with pneumonitis.Results In Group 1, 37 patients (9.7%) developed pneumonitis. KL-6 levels were significantly elevated at irAE onset (pre: 222.0 U/mL, post: 743.0 U/mL, p<0.0001). Receiver operating characteristic curve analysis showed an area under the curve (AUC) of 0.903 (sensitivity 81.1%, specificity 91.6%) with a cut-off value 1.52 times pre-KL-6 levels, indicating that KL-6 is a reliable biomarker for pneumonitis. In these patients, the KL-6 level increased regardless of pneumonitis severity and was significantly elevated in patients with both symptomatic (pre: 205.0 U/mL, post: 674.5 U/mL, p<0.0001) and asymptomatic pneumonitis (pre: 314.0 U/mL, post: 743.0 U/mL, p<0.0001) at irAE onset. After irAE treatment, KL-6 levels in steroid-responsive patients remained unchanged; however, steroid-unresponsive patients had a significant increase in KL-6 levels at 1 month (1078 U/mL, p=0.031) compared with at irAE onset (678.0 U/mL). In Group 2, 24 patients (20.3%) developed irAE pneumonitis, with KL-6 levels elevated (pre: 360.5 U/mL, post: 506.5 U/mL, p=0.029) and an AUC of 0.683, indicating that KL-6 was less reliable in patients with NSCLC.Conclusions KL-6 is a viable screening biomarker in ICI-induced pneumonitis, particularly in patients without NSCLC. In patients with NSCLC, the significance of KL-6 monitoring is limited as it is not effective for detecting ICI-induced pneumonitis; their treatment is typically managed by pulmonary specialists. Early detection through KL-6 monitoring facilitates timely intervention for ICI-induced pneumonitis, potentially preventing treatment interruptions and reducing the need for immunosuppressants.